Peningkatan Hasil Belajar Siswa dengan Model Gallery Walk pada PAI di SMP Negeri 1 Kinali - Ikhwan, Najmi; Nurjanah, Nurjanah (Lembaga Yasin AlSys, 2025)
This study is motivated by the low learning outcomes of students in the Islamic Religious Education (PAI) subject at SMP Negeri 1 Kinali, West Pasaman Regency, primarily due to the use of one-way teaching methods and limited active student engagement. The objective of this research is to improve student learning outcomes through the implementation of the Cooperative Learning model, specifically the Gallery Walk type. The method employed is Classroom Action Research (CAR), conducted in two cycles, each comprising planning, implementation, observation, and reflection stages. The research subjects were 26 eighth-grade students. Data were collected through observations of learning activities, learning outcome tests, field notes, and documentation. The results show that the implementation of the Gallery Walk model significantly improved student learning outcomes. Although the first cycle showed improvement compared to the initial conditions, it did not meet the success indicators. After adjustments in the second cycle, there was further enhancement in student engagement and learning achievements, surpassing the Minimum Mastery Criteria (KKM). Students also demonstrated greater enthusiasm and interest in the learning process. The study concludes that the Cooperative Learning model of the Gallery Walk type is effective in improving student learning outcomes in PAI, while also fostering critical thinking, collaboration, and communication skills.